The effects of green consumer empowerment in advertising on corporate evaluations and purchase intention: the case of organic food - Xisi Yang; Anja Weber; Anna-Katharina Grimm (Review of Managerial Science, 2021)
This research aims to investigate the potential of consumer empowerment, the activation of consumers' perceived power over companies, to achieve improved advertising effects for organic food compared to only communicating ecological benefits (classical green appeals). Two online experiments were conducted to analyze the ad effectiveness for consumers' responses including their evaluations of the company and purchase intentions (nStudy10.167em=0.167em294; nStudy20.167em=0.167em457). Results indicate that green empowerment ads reach overall better performance to increase people's perceived customer orientation and purchase intentions compared to green appeals, while similar effects are identified for perceived corporate environmental responsibility. Empowerment tactics are especially effective when consumers perceive the supplier to be a larger, high-resource company compared to a smaller, low-resource one. The significant effects of perceived corporate resources also indicates that smaller companies should use differentiated ad strategies depending on if they intend to enhance consumers' purchase intentions or their environmental reputation.
Keywords: P25; P15; 650; Green advertisement; Consumer empowerment; Customer orientation; Organic food